Child and Teacher Attachment Relationship - Ode Yahyu Herliany Yusuf; Ade Wahyu Ningsih; Irma Fatika Sari; Wa Ode Warti; Dewi Dewi; Wa Harni (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The attachment relationship between children and teachers consists of three types of relationships, namely secure attachment relationships, insecure attachment relationships, and ambivalent or insecure resistant attachment relationships. In forming a good bond with children, teachers must have a secure attachment with children. Attachment or attachment is a relationship between two people who have a strong relationship and a good emotional bond. A secure attachment between children and teachers will have a positive impact on children until children become adults.